Selection of fungal endophytes with biocontrol potential against Fusarium head blight in wheat - Rojas, Edward C.; Jensen, Birgit; Jørgensen, Hans J.L.; Latz, Meike A.C.; Esteban, Pilar; Ding, Yuwei; Collinge, David B. (Biological control, 2020)
•Endophytes were isolated from healthy wheat spikes in areas of high FHB incidence.•15 isolates were selected for biological control screening.•Four isolates were identified as potential biocontrol agents against Fusarium graminearum infection on detached wheat spikelets and on greenhouse assays.•Isolates reduced up to 70% of FHB severity when inoculated prior the pathogen.•The strains were identified as: Sarocladium strictum C113L, Anthracocystis floculossa P1P1, Anthracocystis floculossa F63P and Penicillium olsonii ML37. Fusarium head blight (FHB) is a major disease in wheat and other cereal crops. Biological control is a promising alternative for control of this disease as current control options are not efficient. Fungal endophytes could represent a new source of biological control agents since they colonise plant tissues asymptomatically whilst sharing the same biological niche as pathogens. Here, we show that healthy wheat spikes and leaves collected in areas with high FHB incidence harbour fungal isolates that reduce disease severity and pathogen biomass inside the spikes. We employed an in planta screening method using detached spikelets to observe the performance of 15 fungal strains against Fusarium infection. The results were validated in greenhouse spike inoculation assays. Isolates Sarocladium strictum C113L, Anthracocystis floculossa P1P1, A. floculossa F63P and Penicillium olsonii ML37 were identified as potential biocontrol agents of FHB in wheat. Timing of application was important: the endophytes needed to be applied at least two days before the pathogen to have a significant effect. Reduced symptom expression correlated with reduced biomass of Fusarium graminearum in the infected spikelets. Interestingly, none of these isolates reduced Fusarium growth in confrontation assays on agar plates. Our results suggest that naturally occurring endophytes could be a new source of biological control agents to be used in integrated pest management strategies.